The Influence of Intellectual Intelligence, Work Motivation and Machiavellian on Creative Accounting Practices - Sukamto, Sukamto; Wahyuni, Wiwin; Marpurdianto, Kharis (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2024)
Creative accounting is unethical because it manipulates financial data, but there are also those who think that creative accounting is allowed as long as it does not contradict generally accepted accounting principles, for example, simplifying several forms of reports or merging a cost into one other cost because it is considered rare. Accounting students have a strong relationship with the problem to be researched, so the researcher uses students. Intellectual Intelligence (IQ) is a term used to measure the level of intelligence of an individual. The higher a person's IQ, the higher his or her ability to deal with problems related to spatial, numerical, and linguistic abilities. Work motivation is something that causes motivation or work spirit that is influenced by several factors, including superiors, physical facilities, policies, regulations, monetary and non-monetary service rewards, types of work and challenges. The Machiavellian nature is also a factor that can cause individuals to practice creative accounting which is an unethical act. Although many researchers disagree with creative accounting practices, there are also a few researchers who have a different perception that creative accounting practices do not include fraudulent acts, it is a matter of one's interpretation and occurs because of the use of loopholes in the standards